Analysis of the Structure and Dynamics of Economic Growth in Pohuwato Regency Using the Location Quotient and Shift Share Approaches - Ramadhani, Bulan Suci; Hawanda Metania Cono, Titi (Jurnal Ilmu Ekonomi JIE, 2025)
Regional economic development plays a vital role in improving the quality of life and community welfare, but each region has a distinct economic structure shaped by its potential and characteristics. This study aims to analyze the structure and dynamics of the economy of Pohuwato Regency, Gorontalo Province. This research uses Location Quotient and Shift Share methods, combined with qualitative interviews at Bappeda Pohuwato. The results of the analysis show that Pohuwato's economy is still dominated by the Agriculture, Forestry, and Fisheries sector and the Processing Industry as the base sector. However, the agricultural sector tends to be less competitive, as it relies on raw commodities, whereas the processing industry performs well and is highly competitive. Shift Share analysis reveals a shift to rapidly growing non-base sectors, particularly trade, construction, and health services. This finding confirms the economic transformation in Pohuwato Regency from a traditional, agriculture-based dominance to a more diverse, competitive, and sustainable economic structure, which requires support from downstream and economic diversification strategies.